Analysis of the Stages of Establishing an Individual Business in the City of Medan - Agus Rahmadsyah; Aldira Lidwina Br Sembiring; Kennedy Prabowo Eko; Anry Situmorang; Reva Rizky Aulia (Asian Journal of Applied Business and Management, 2023)
The development of medium-scale individual businesses that were established aims to increase the potential and seek profits from running one's own business. The method used in this study is the method of direct interviews with business owners to achieve the results of the interview. From the interviews that have been conducted, several things were obtained, namely individual businesses have their own target market and express ideas, and their own innovation for the sustainability of the business being run. Individual businesses that are run must be well developed with good marketing and strategies to achieve maximum business.